Characterizing the Ideal Audio-Visual Learning Content of Writing Course Learned in Distance - Patahuddin Patahuddin; Syawal Syawal; Chester Esnara; Muhaimin Abdullah (Lingua Cultura, 2022)
The research aimed to discuss the need for a learning tool that was capable of presenting audio and visual aids to accommodate students in learning writing. It was urgently needed as a logical consequence of the COVID-19 pandemic, which disallowed face-to-face learning to be conducted. The research was conducted at the Department of English Education, Faculty of Teachers Training and Education, Universitas Muhammadiyah Parepare, by utilizing a questionnaire to explore the characteristics of ideal writing material restricted to visual aids. The research was participated by the second and fourth-semester learners as the population and recruited the samples based on simple random sampling. Every individual in the population had an equal chance to be chosen as a sample. There were 30 undergraduate students who enrolled in basic writing and advanced writing courses who became the subject of the research. Based on the research findings, eight characteristics of good audio visuals are recommended by the students. Those characteristics include the visual and audio elements/items, creative and innovative content, language and expression, operations and mechanisms (various learning opportunities and preferences), and eye-catching form/shape/design, which deliver brief and clear learning material under several considerations. Furthermore, following the findings, it also indicates that the effectiveness of delivering audiovisual aids materials in the learning process depends on how clear the audiovisual item (i.e. the text and audio, how efficient the material and audiovisual durations provided, how interesting and well-organized the design to attract students’ learning intention, how good the visual quality and how the audiovisual) can be produced into a small size to minimize the use of internet data. The research concludes that audiovisual learning materials need to be selectively chosen and periodically and systematically evaluated to best facilitate students in dealing with writing.